1973
DOI: 10.1530/jrf.0.0340149
|View full text |Cite
|
Sign up to set email alerts
|

INCREASE OF (Ca2+-Mg2+)-ADENOSINE TRIPHOSPHATASE ACTIVITY IN RAT TESTIS UNDERGOING REGRESSION OF THE GERMINAL EPITHELIUM

Abstract: The pattern of testicular energy metabolism changes when spermatogenesis is impaired. Testes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Like other mammals, alkaline phosphatase, acid phosphatase and adenosine triphosphatase were mainly demonstrated in all the elements of germinal epithelium of seminiferous tubules and Sertoli cells of the testis of the musk shrew (Singh and Mathur -1968). Delhumeau-Ongay et al (1973) had noticed that increase in testicular ATPase activity is associated with the regression of germinal epithelium. A decrease in testicular ATPase activity with advancing age is also attributed to decrease in spermatogenic activity (Ikegwuonu and Aire -1977).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Like other mammals, alkaline phosphatase, acid phosphatase and adenosine triphosphatase were mainly demonstrated in all the elements of germinal epithelium of seminiferous tubules and Sertoli cells of the testis of the musk shrew (Singh and Mathur -1968). Delhumeau-Ongay et al (1973) had noticed that increase in testicular ATPase activity is associated with the regression of germinal epithelium. A decrease in testicular ATPase activity with advancing age is also attributed to decrease in spermatogenic activity (Ikegwuonu and Aire -1977).…”
Section: Discussionmentioning
confidence: 97%
“…Specific enzymes have been suggested as possible markers for the study of physiology of particular cell types of the testis (Hodgen -1977). The association of acid phosphatase, alkaline phosphatase and adenosine triphophatase with the physiology of the seminiferous tubules were inferred from alteration in their activities after suppression of germ cells in various experimental and functional conditions (Males and Turkington -1971;Tice and Barnett -1963;Delhumeau-Ongay et al -1973;Guha and Vanha-Perttula -1980). It has been suggested that testosterone plays an important role in the maintenance and differentiation of germ cells (Steinberger and Steinberger -1974;Vernon et al -1975;Marshall et al -1986).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in activity of acid phosphatase in the testes at days 40 and 70 can be supposed to be brought about with the depletion of cell population of the seminiferous tubules of the treated rats. Earlier studies have shown that the alteration in the activities of testicular phosphatase can be reflected with the suppression of functional changes in the testicular cell types [8,11,23,34].…”
Section: Discussionmentioning
confidence: 99%